Secreted Autotransporter Toxin (Sat) Mediates Innate Immune System Evasion - Freire, Claudia A.; Silva, Rosa M.; Ruiz, Rita C.; Pimenta, Daniel C.; Bryant, Jack A.; Henderson, Ian R.; Barbosa, Angela S.; Elias, Waldir P. (Frontiers in Immunology, 2022)
Several strategies are used by Escherichia coli to evade the host innate immune system in the blood, such as the cleavage of complement system proteins by secreted proteases. Members of the Serine Proteases Autotransporters of Enterobacteriaceae (SPATE) family have been described as presenting proteolytic effects against complement proteins. Among the SPATE-encoding genes sat (secreted autotransporter toxin) has been detected in high frequencies among strains of E. coli isolated from bacteremia. Sat has been characterized for its cytotoxic action, but the possible immunomodulatory effects of Sat have not been investigated. Therefore, this study aimed to evaluate the proteolytic effects of Sat on complement proteins and the role in pathogenesis of BSI caused by extraintestinal E. coli (ExPEC). E. coli EC071 was selected as a Sat-producing ExPEC strain. Whole-genome sequencing showed that sat sequences of EC071 and uropathogenic E. coli CFT073 present 99% identity. EC071 was shown to be resistant to the bactericidal activity of normal human serum (NHS). Purified native Sat was used in proteolytic assays with proteins of the complement system and, except for C1q, all tested substrates were cleaved by Sat in a dose and time-dependent manner. Moreover, E. coli DH5α survived in NHS pre-incubated with Sat. EC071-derivative strains harboring sat knockout and in trans complementations producing either active or non-active Sat were tested in a murine sepsis model. Lethality was reduced by 50% when mice were inoculated with the sat mutant strain. The complemented strain producing active Sat partially restored the effect caused by the wild-type strain. The results presented in this study show that Sat presents immunomodulatory effects by cleaving several proteins of the three complement system pathways. Therefore, Sat plays an important role in the establishment of bloodstream infections and sepsis.